Virtual Acoustic Characterization of a Multipurpose Sports Facility: A Case Study of the Coliseum at “Unidad Educativa Municipal Sebastián de Benalcázar”, Quito, Ecuador - L S Jácome; P Simbaña; G Cadena (IOP Publishing, 2024)
This study presents a virtual acoustic characterization of a multipurpose sports facility, focusing on a case study of the coliseum at “Unidad Educativa Municipal Sebastián de Benalcázar” in Quito, Ecuador. Utilizing a non-intrusive, simulation-based approach, an initial detailed survey of the coliseum’s interior was conducted. AutoCAD and SketchUp software were utilized to generate a three-dimensional (3D) model based on the acquired data. This model was then exported to ODEON software for acoustic simulation. Important acoustic parameters, including reverberation duration, clarity, STI (Speech Transmission Index), and RASTI (Rapid Speech Transmission Index), were obtained from the simulation. These parameters were instrumental in characterizing the sports facility’s acoustic quality and comparing it with established reference values. Special emphasis was given to the initial parameters of reverberation time and STI, crucial for assessing the acoustic quality of the space. This virtual characterization provides significant insights into the acoustical properties of the coliseum, highlighting its potential and limitations as a multifunctional sports venue. The present study makes a significant contribution to the field of virtual acoustic assessments by providing a comprehensive framework for future improvements in the acoustic design and sound quality of similar environments. The study specifically addresses the distinct geographical and architectural context of Quito, Ecuador.
Keywords: Clarity; Multipurpose sports facility; RASTI; Reverberation time; STI; Virtual acoustic characterization